Bernard Lahire's Microsociology and Research in Ead: through a Unique Reading of the Trajectories of Higher Distance Education in the State of Goiás: Por una Lectura Particular de las Trayectorias de Educacion Superior a Distancia en el Estado de Goiás - Quiroga, Fernando Lionel (2025)
In view of the various themes that constitute the field of distance learning in the Brazilian educational scenario, a theoretical-conceptual gap can still be seen regarding the trajectories and experiences of students in this modality. In this sense, it is a crucial demand not only to improve the aspects inherent to technologies and teaching processes (didactics, methodologies and approaches), but also to support data that can guide the formulation of public policies aimed at this segment. Our objective, therefore, was to demonstrate the relevance and urgency of a unique understanding of the aspects that constitute the distance learning experience in individual trajectories and how Bernard Lahire's (2017) microsociological perspective can contribute to the constitution of a theoretical corpus that provides account of this reality. This inaugural aspect establishes, so to speak, the demand for a refined understanding of the processes that require the student to reconfigure domestic spaces, related to an “art of doing” and that have a decisive impact on improving the living conditions of the State of Goiás.   Keywords: Distance education. University education. Microsociology. Trajectories. Research Methodology.